Doing isolation – Caring Citizens. A cross-country comparative analysis of patient experiences with isolation practices during the early phase of the Covid-19 pandemic - Christine Holmberg; Sarah Nettleton; Rika Sakuma Sato; Vinita Mahtani-Chugani; Annelieke Driessen; lja Ormel; Madison Wynn; Nienke Verhej; Manna Alma; Anne Thier (SSM: Qualitative Research in Health, 2023)
The aim of this article is to investigate isolation experiences of individuals affected by Covid-19 and explore how care practices were enacted or upheld under the particular policies of the pandemic. Conceptually we draw upon Foucault's notion of biopolitics and scholarship on ‘care practices’ and ‘carescapes’. We are interested in how theoretical ideas such as ‘containing the virus’ or ‘flattening the curve,’ as part of policies of ‘pandemic management,’ shaped lived realities and influenced practices and understandings of care. We reviewed qualitative interviews with individuals who were ill with Covid-19 in 2020/2021 from seven countries that we analyzed comparatively across emerging themes with a Foucauldian lens on biopolitics.The idea of ‘carescapes,’ suggests that ‘care’ and ‘policy’ intermingle, which allow us to bring to the fore what is silenced through the biopolitics of Covid-19. Carescapes are the embodied places of care where policies and regulations traverse from public into private spaces, effectively re-configuring the latter. To ‘do’ isolation in the context of Covid-19, carescapes were assembled with the help of material things such as, masks, disinfectants, doors and schedules; these served as boundaries that had to be sustained and navigated. ‘Doing isolation’ therefore presents a form of biopolitics that relies on individual citizenship and complex care practices required to chart the terrain created by the polices of the pandemic. Doing isolation was especially challenging because policies about safe spaces and safe practices were regularly changed as governments struggled to devise policies to contain the pandemic.